소비자의 조절모드와 희소성 메시지가 패션제품평가에 미치는 영향 - 백소라; So Ra Baek; 황선진; Sun Jin Hwang; 여준상; Jun Sang Yeo (The Research Journal of the Costume Culture, 2014)
This study looked into the scarcity effect based on the consumers` self-regulatory modes and determined the effect that such a regulatory mode and that quantity-scarcity messages would have on evaluations of fashion products. To that end, the study used a 2 (regulatory mode: assessment mode/locomotion mode)×2 (message type: quantity-scarcity message/non-scarcity message) between-subjects factorial design in which buying impulsiveness was presented as a mediator variable that showed differences in product evaluations depending on the message type and on the presence of a self-regulatory mode. The results of this study showed that locomotion-oriented consumers evaluated products more positively compared to assessment-oriented consumers when the quantity-scarcity message was presented. When a non-scarcity message was presented, no significant difference was observed in product evaluations based on the consumers` self-regulatory modes. In addition, buying impulsiveness in consumers served a mediator role in the evaluations of fashion products. The results of this study imply that a clear understanding of consumers is a prerequisite for maximizing the scarcity effect and that companies need to differentiate in terms of the way they use scarcity messages based on consumers` self-regulatory modes.